Colorful God and Goddess as the representation of modern Greek mythology in Lore Olympus - Afidah, Ari; Agustina, Mia Fitria; Trisnawati, Ririn Kurnia (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2022)
Lore Olympus is a webtoon that uses color as a sign for each of its characters. In interpreting symbols, this study applies Peirce's semiotic theory related to representamen or signs, objects, and interpretants. This study aims to describe the meaning of colors in the six characters of gods and goddesses in Lore Olympus. This research used qualitative methods. It was found that the colors in the six characters of gods and goddesses had a general and specific meaning that were used to convey their personalities. The blue color symbolizes Hades's cold personality, the pink color represents Persephone's kindness, the green color represents Demeter's overprotective personality, the purple color represents Zeus as the king of the gods, the yellow color symbolizes Hera's cheerful and jealousy, and lastly, the red color symbolizes Hermes's extroverted and passionate personality. Finally, it is hoped that this study can create more insight into color as an aspect that can affect personality.Keywords: colors, Lore Olympus, semiotic, symbol